EFFECT OF WOOD-LOAD WOOD-LOADING PROCEDURES (Manihot esculenta Crantz) ON PADI CONTENT AND QUALITY OF UVAN WOOD FLOUR - Wika Rinawati (Jurnal Penelitian Saintek, 2003)
This research is about flouring procedures,  which do with three ways.First  (grating  and  drying).  Second  (grating,  parting   of  starch  and waster). Third (grating and drying of waster). Goals from  this research are: 1) to know cassava's flour  starch  based on difference of flouring procedure 1, II,  and 111,2)  to know about impact of flouring procedure difference 1, 11,   and 111on cassava's flour  starch  compared with fresh cassava, and 3) to know the impact of flouring procedure difference 1, 11 and 111on quality (colour and smell) cassava's flour.  Research were did at  Food   Biochemical  Laboratory   Farm   Technology  Gadjah   Mada University  to  analyze flour   and  Culinary  Laboratory,  Family  Life Education, Technique Faculty, Yogyakarta State University, where flour product  was made. Research start  with make  a starch  with starching procedure  1, 11,    and  111 and  continued  with  analyzing  cassava  and sensoric test of cassava's flour quality which depend on colour and smell. The research show that: 1) cassava's flour  starch in 1 way 86.69%, 11is87.94%,  111 is  87.I4%.  2)  there  is  impact  of flouring  procedure  on cassava's flour starch compared with fresh starch. There is no difference impact offlouring procedure 1, II, and IlIon  cassava's starch flour at 1% significantly.  3)  There is  impact on flouring  procedure   difference  on colour and smell cassava's flour at 1% significantly.